The teaching of Human and Social Sciences with adolescents deprived of freedom: An experience about the “Month” of Black Consciousness - Reges, Areillen Ronney Rocha; Medeiros, Emerson Augusto de; Santos, Jean Mac Cole Tavares (Revista Hipótese, 2023)
This article presents an experience lived within the context of the COVID-19 pandemic, with adolescents deprived of liberty, in the socio-educational school context within the confinement setting of the Socio-Educational Assistance Center (CASE), Mossoró – RN. The experience revolves around teaching Human and Social Sciences, focusing on an occasion during Black Consciousness Month in the year 2020. Furthermore, it emphasizes the understanding of the importance of this field within the educational, scientific, and social realms, as demonstrated through the account provided, grounded in authors who engage in discussions on the central theme, namely Julião (2020), Chizzotti (2016a), Lucindo and Gonzaga (2016), Gomide (2013), Paiva (2009), Assmann (1998), Freire (1970), among others. In conclusion, we allude that, among other aspects, this field has become indispensable in the construction of knowledge and the reintegration of the socio-educational participants.